Silagem de ração total na alimentação de equinos - Julia Andressa Boufleur (2024)
The total ensiled feed or diet, composed of roughage, concentrates and additives, has emerged as an innovative alternative for use in feeding horses raised in a semi-intensive system. The objective of this study was to evaluate the replacement of conventional feed with total feed silage (Equibalance®) on nutrient digestibility, feeding behavior, blood parameters and fecal quality of horses at working level. The experimental design was the Latin square (4 x 4) composed of four treatments elaborated according to the inclusion levels of the total diet (Equibalance®), being: conventional (CO) - 1.5% body weight (BW) of tifton hay 85 and 0.5% BW concentrate; (SR10) - 1.5% BW of Tifton 85 hay, 0.3% BW of concentrate and 0.2% BW of Equibalance®; (SR30 - 1.5% BW of Tifton 85 hay and 0.6% BW of Equibalance® and SR100 - 100% inclusion of Equibalance®. The diets were balanced to meet the requirements of horses in light work, according to the NRC (2007). A nutrient digestibility test was carried out through total feces collection. Blood samples were also collected to evaluate serum concentrations of Na, K, Cl, lactate and glucose and fecal samples to perform pH All statistical analyzes were performed using the SAS University statistical program (2016), and means were compared using the Tukey test at 5% significance. For blood parameters (glucose, lactate and electrolytes), there was a difference (P < 0.01) between treatments and time. There was no difference (P >0.01) between treatments CO and SR10, but they differed from treatments SR30 and SR100, which did not differ between themselves and presented values closer to baseline values. As for the times, time -5 did not differ from times 30 and 60, but it was different from the others. Times 90 to 300 min did not differ. There was no treatment effect for fecal pH (P > 0.59) and the average value was 6.38 ± 0.06. There was a significant effect (P<0.01) for nutrient digestibility coefficients, the SR100 treatment showed a higher digestibility coefficient for the nutrients DM, CP, EE and MM, compared to the other treatments. The CO, SR10 and SR30 treatments did not differ from each other for NDF digestibility values, but presented higher values than the SR100 treatment. For nutrient intake, there was a significant effect (P<0.01): the CO, SR10 and SR30 treatments did not differ from each other for the nutrients DM, CP and MM, but presented higher values than the SR100 treatment. For NDF intake values, the CO and SR10 treatments did not differ (P>0.01) and presented higher means than the SR30 and SR100 treatments, which also differed from each other (P<0.01). The use of total feed silage did not negatively alter blood parameters or fecal pH, and improved the digestibility of most nutrients, although presenting lower nutrient intake. Therefore, it can be used in up to 100% inclusion in equine nutrition.